Palladium-catalyzed oxidative homocoupling of pyrazole boronic esters to access versatile bipyrazoles and the flexible metal–organic framework Co(4, 4′-bipyrazolate). Issue 8 (3rd January 2020) - Taylor, Mercedes K.; Juhl, Martin; Hadaf, Gul Barg; Hwang, Dasol; Velasquez, Ever; Oktawiec, Julia; Lefton, Jonathan B.; Runčevski, Tomče; Long, Jeffrey R.; Lee, Ji-Woong
Abstract : A facile catalytic protocol achieves the homocoupling of pyrazole boronic esters, enabling access to the structurally-flexible metal–organic framework Co(bpz). Abstract : A facile route to 4, 4′-bipyrazole (H2 bpz) and other symmetric bipyrazoles is achieved via the palladium-catalyzed homocoupling of a pyrazole boronic ester in the presence of air and water, enabling us to provide the first crystal structures and evidence of structural phase changes in the bipyrazolate-based metal–organic framework Co(bpz).